Implementasi konsep Islam Rahmatan Lil’alamin dalam kehidupan bermasyarakat - Anam, Rifky Khoirul (Maliki Interdisciplinary Journal, 2025)
This article aims to explain the Islamic concept of rahmatan lil 'alamin, how to implement it in daily life and the challenges faced by Muslims in realizing it. Islam rahmatan lil'alamin is a concept that strengthens that Islam comes to bring love and benefits to all beings of nature. This concept is based on the verses of the Qur'an and the sunnah of the Prophet Muhammad SAW which emphasizes justice, tolerance, and balance. This study uses a literature study method. Data analysis is carried out after collecting from various sources, namely by reducing data, presenting data, and drawing conclusions. The implementation of rahmatan lil'alamin can be seen in interreligious relations through tolerance and dialogue, environmental protection by maintaining the balance of the ecosystem, a fair economic system, and education aimed at educating and shaping morals. However, challenges such as radicalism, environmental damage, and social disparities still hinder the realization of this mission. For this reason, a deep understanding and collective steps from Muslims are needed in facing this challenge to create a peaceful and balanced world in accordance with Islamic values.